Replication of genome-wide association studies on asthma and allergic diseases in Korean adult population - Dankyu Yoon (BMB Reports, 2012)
Allergic diseases such as asthma, allergic rhinitis, and atopicdermatitis are heterogeneous diseases characterized by multiplesymptoms and phenotypes. Recent advancements in geneticstudy enabled us to identify disease associated genetic factors.Numerous genome-wide association studies (GWAS) have revealedmultiple associated loci for allergic diseases. However,the majority of previous studies have been conducted in populationsof European ancestry. Moreover, the associations of singlenucleotide polymorphisms (SNPs) with allergic diseaseshave not been studied amongst the large-scale general Koreanpopulation. Herein, we performed the replication study to validatethe previous variants, known to be associated with allergicdiseases, in the Korean population. In this study, we categorizedthree allergic related phenotypes, one allergy and two asthmarelated phenotypes, based on self-reports of physician diagnosisand their symptoms from 8,842 samples. As a result, we foundnominally significant associations of 6 SNPs with at least one allergicrelated phenotype in the Korean population. [BMB reports2012; 45(5): 305-310]